Morphological phenotype of macrophages in response to lidocaine, interleukin 1β, and lipopolysaccharide - Muurama, Veera (My University, 2025)
The morphological differences of macrophages in different culturing conditions are still unclear. However, novel studies have suggested that the activation of tissue-resident macrophages in inflammation plays a crucial role in chronic pain. Dorsal root ganglia convey pain signals from the periphery towards the central nervous system. Macrophages induce pain via interactions with nociceptors through chemical mediators, such as tumor necrosis factor α and interleukin 1β. The morphological phenotype of macrophages alters based on the activation state of the cell which contributes to increasing pain. Pain-inducing macrophages express an increased cell area, and a rounder shape based on previous literature. This research was conducted by stimulating macrophages in vitro conditions with lidocaine, interleukin 1β, and bacterial lipopolysaccharide. With the help of immunostaining, fluorescence imaging, and image analysis, the number and morphology of the macrophages were compared against controls. The cell area of macrophages was found to be increased after the addition of lipopolysaccharide. However, none of the used compounds had a significant impact on the roundness of the macrophages. In addition, most of the macrophages did not survive in the co-culture platform cultured with primary sensory neurons. This research assisted in finding the relationship between the activation of macrophages and its connection to neuronal activity in chronic pain disorders. More research is needed to confirm the results and the development of new drugs for treating inflammatory pain.
Keywords: pain, macrophage, dorsal root ganglion, lidocaine, IL-1β, LPS